Catalytic deoxygenation with SO42--Fe2O3/Al2O3 catalyst: Optimization by Taguchi method - Shafihi U.; Hafriz R.S.R.M.; Arifin N.A.; Nor Shafizah I.; Idris A.; Salmiaton A.; Razali N.M. (Elsevier B.V., 2024)
This work investigates the optimization of reaction parameters with the Taguchi method for catalytic deoxygenation of waste cooking oil (WCO) as an alternative renewable fuel process. Commercial sulphated-ferric (II) oxide/alumina oxide catalyst has the potential as a deoxygenation catalyst due to its good physicochemical properties which enhance the removal of oxygenated species. The obtained pyrolysis oil analysed by GC-MS revealed the selectivity of the pyrolysis oil mostly in the range of light diesel and kerosene fraction. From an analysis of variance (ANOVA), temperature awarded the most significant impact (86.62%) in this catalytic deoxygenation as compared to three other parameters followed by reaction time > N2 flow > catalyst loading. From the GC-MS analysis, the maximum renewable diesel fraction of 49.66% was obtained at 400 C, 1 wt% of catalyst, 90 min of reaction time and 20 cm3/min N2 flow. The predicted model by Taguchi in the present study validated by the experimental work shows a promising application in optimising the catalytic pyrolysis process for future use. 2023 The Authors